Chemical, Manufacturing, and Standardization Controls of Grape Polyphenol Dietary Supplements in Support of a Clinical Study: Mass Uniformity, Polyphenol Dosage, and Profiles - Lyu, Weiting; Rodriguez, David; Ferruzzi, Mario G.; Pasinetti, Giulio M.; Murrough, James W.; Simon, James E.; Wu, Qingli (Frontiers in Nutrition, 2021)
The bioactive dietary polyphenols in grape (Vitis vinifera) have been used in Dietary Supplements (DS) with the aim to prevent numerous diseases including cardiovascular, neurodegenerative diseases and to reduce depression and anxiety. Given prior recognition that dietary supplements can be quality challenged from purity, authentication, adulteration, and actual concentration of targeted bioactives, to ensure consumer health protection as well as the quality and safety of grape polyphenol-based DS, the present investigation was aimed at establishing a comprehensive quality control approach for grape polyphenol-based DS in support of a human clinical study. In this work, manufactured grape seed polyphenol extract (GSPE) and trans-resveratrol (RSV) capsules, and Concord Grape Juice (CGJ) along with the corresponding original drug materials were analyzed using different LC/UV-Vis/MS (Liquid chromatography/ Ultraviolet–visible spectroscopy/ Mass spectrometry) methods developed. Weight variation of GSPE and RSV capsules were also evaluated according to the United States Pharmacopeia (USP) tests. The results indicate that total identified polyphenols content in each GSE capsules / CGJs were very similar, and all GSE / RSV capsules passed the content / weight uniformity test. Given the complexity of these and many botanical products from issues of purity, quality, adulteration, consistency and coupled to the complex chemistry in each grape-derived botanical, the assurance of quality and steps needed to ensure that grape-derived dietary supplements are well homogeneous, stable, and contain the known and expected bioactives at specific concentration ranges are fundamental to any research study and in particular to a clinical trial. Each of these issues are essential to provide a solid foundation upon which clinical trials with botanicals can be conducted with the goal of realizing measurable mental health outcomes such as reducing depression and anxiety as well as understanding of their underlying biological mechanisms.